2021
DOI: 10.4236/me.2021.1210074
|View full text |Cite
|
Sign up to set email alerts
|

ABC-VEN Analysis of Medicine Expenditure at Mwananyamala Regional Hospital in Tanzania

Abstract: Policymakers in developing countries are looking for effective and efficient ways to control hiking expenditure on medicines. This article shows the effectiveness of the ABC-VEN method to improve efficiency in resource use with data from Mwananyamala hospital in Tanzania. We used expenditure data for 233 medicines worth 909.9 million Tsh (392,386.4 USD) bought in the year 2018/2019. Data were extracted from the electronic system, receipts, and other relevant documents. Medicines were categorized according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Omeprazole was ranked among the top medicines with high expenditure, possibly resulting in prescription habits. A study conducted in Tanzania at Mwananyamala regional hospital found the same results while investigating whether proton pump inhibitors, including omeprazole, are among products with high expenditure [ 10 ].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Omeprazole was ranked among the top medicines with high expenditure, possibly resulting in prescription habits. A study conducted in Tanzania at Mwananyamala regional hospital found the same results while investigating whether proton pump inhibitors, including omeprazole, are among products with high expenditure [ 10 ].…”
Section: Discussionmentioning
confidence: 84%
“…However, with a frequent shortage of medicines, it would not be easy to ensure the best healthcare service delivery [ 5 8 ]. Thus, effective inventory management is needed to match the cost of stocks with the demand for medicines [ 3 , 9 , 10 ]. Optimal medicines management helps ensure that essential drugs are available at affordable prices [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…A single AN item (Valganciclovir HCL 450 mg tablet) in the present study consumed 9.4% of the annual expenditure in 2014/15. In a similar study conducted at Mwananyamala hospital in Tanzania, four of 233 medicines, which accounts for 7% of the total medicine expenditures, were expensive and nonessential ( Mori et al, 2021 ). This subgroup (expensive and nonessential) needs removal from the list if possible or replacement with equivalent but less costly medicine; hence, it would bring cost savings without affecting patient care ( Kokonya, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…71,943,426(Darmawan et al, 2021). Efficient investment in drug supply value can be realized through rational prescribing and replacement of high-cost and non-essential vital drugs with low-cost ones (Mori et al, 2021). Effective and efficient management of pharmacies requires efficient prioritization and proper decision-making in the purchase and distribution of drug items and close supervision of those classified as important categories (Fitriana et al, 2017).…”
Section: Cost Efficiency After Inventory Planning Using Abc-ven and E...mentioning
confidence: 99%